2021
DOI: 10.1128/iai.00735-20
|View full text |Cite
|
Sign up to set email alerts
|

Ectopic Expression of Human Thymosin β4 Confers Resistance to Legionella pneumophila during Pulmonary and Systemic Infection in Mice

Abstract: Thymosin beta-4 (Tβ4) is an actin-sequestering peptide that plays important roles in regeneration and remodeling of injured tissues. However, its function in a naturally occurring pathogenic bacterial infection model has remained elusive. We adopted Tβ4-overexpressing transgenic (Tg) mice to investigate the role of Tβ4 in acute pulmonary infection and systemic sepsis caused by Legionella pneumophila. Upon infection, Tβ4-Tg mice demonstrated significantly lower bacterial loads in the lung, less hyaline membrane… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 53 publications
1
3
0
Order By: Relevance
“…Most patients with diabetes have abnormal protein and fat metabolism, which can lead to increased body consumption, decreased muscle strength, respiratory muscle atrophy, reduced deep breathing function and cough ability, thus increasing the risk of lung infection. 21 Mechanical ventilation duration was an independent risk factor of pulmonary infection in our study. Similarly, Zhang et al 22 showed that mechanical ventilation time ≥3 days in ICU patients is a risk factor for pulmonary infection.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…Most patients with diabetes have abnormal protein and fat metabolism, which can lead to increased body consumption, decreased muscle strength, respiratory muscle atrophy, reduced deep breathing function and cough ability, thus increasing the risk of lung infection. 21 Mechanical ventilation duration was an independent risk factor of pulmonary infection in our study. Similarly, Zhang et al 22 showed that mechanical ventilation time ≥3 days in ICU patients is a risk factor for pulmonary infection.…”
Section: Discussionsupporting
confidence: 53%
“…Most patients with diabetes have abnormal protein and fat metabolism, which can lead to increased body consumption, decreased muscle strength, respiratory muscle atrophy, reduced deep breathing function and cough ability, thus increasing the risk of lung infection. 21 …”
Section: Discussionmentioning
confidence: 99%
“…The problem that could arise is how to simply measure the mitochondrial function in people. About this issue, it should be highlighted that in our study the correlation analysis showed positive relation between mitochondrial membrane potential and the levels of plasma Thymosin β4, which is an anti-inflammatory hormone that can down-regulate chemokines and cytokines, as well as increase fibrinolysis ( Park et al, 2021 ).…”
Section: Discussionmentioning
confidence: 69%
“…Thymosin beta‐4 (Tβ4), a 43‐amino acid peptide, is involved in multiple cellular responses and plays dual roles in antimicrobial and immune modulation (Park et al ., 2021). Tβ4 has shown potential antimicrobial effects against various bacteria, including E. coli, Staphylococcus aureus , Pseudomonas aeruginosa, and Staphylococcus epidermidis (Tang et al ., 2002; Huang et al ., 2007; Schillaci et al ., 2016; Carion et al ., 2020) and downregulates inflammation.…”
Section: Introductionmentioning
confidence: 99%